Understanding the Impacts of Diversification on Financial Performance and Sustainability: A Case of South Asian Microfinance Institutions - Naureen Afzal; Muhammad Shaukat Malik (Al-Qanṭara, 2023)
The concept of microfinance has gained much importance as it can effectively eradicate poverty of deprived segments and achieve economic development especially in developing economies. Microfinance institutions (MFIs) are observed to have a hybrid objective of both social and financial nature. Existing literature has ignored some essential dimensions of diversification that can influence the financial performance of microfinance institutions. This study collected data from the World Bank for 152 South Asian microfinance institutions for the time period 2012-2019. This research has employed GMM approach with xtabond2 command and findings of the study reveal the significant impacts of various dimensions of diversification for sustainability of microfinance institutions. This study suggests that commercialization of MFIs and adoption of technological advancements has emerged as a result of enormous drop in subsides and donations that doubted goal of sustainability and profitability. Thus, all MFIs generate income through both financial and non-financial services. This has also led to their expansion of social outreach as well as decrease in their operational cost and hence, high financial performance and ultimately sustainability. These findings recommend that microfinance institutions have to pay attention to formulate various policies and offer more diversified services to attain their hybrid objective.